PENANAMAN SIKAP RELIGIUS MELALUI TRI KAYA PARISUDHA PADA SISWA SMP SARASWATI SERIRIT - Feranti, Kadek Wiwin; Prapnuwanti, Luh Purnamasuari; Gunawan, I Ketut Pasek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of students’ religious attitudes has become one of the major educational challenges amid rapid technological advancement and increasingly complex social changes. The cultivation of religious values cannot merely rely on the cognitive delivery of religious instruction but requires a continuous process of value internalization through habituation, role modeling, and sustainable learning experiences. The Hindu teaching of Tri Kaya Parisudha, consisting of Manacika (good thinking), Wacika (good speech), and Kayika (good conduct), has significant relevance to fostering students’ religious character within Hindu educational settings. This study aimed to analyze the strategies employed by Hindu Religious Education teachers in cultivating students’ religious attitudes through Tri Kaya Parisudha, identify implementation challenges, and examine its impact on students’ religious attitude development at SMP Saraswati Seririt. This study employed a qualitative approach using a phenomenological design. Data were collected through observation, in-depth interviews, documentation, and literature review. The primary research instrument was the researcher as a human instrument, supported by observation guidelines, interview guidelines, and documentation. Data analysis employed the Miles and Huberman model involving data reduction, data display, and conclusion verification. The findings revealed that the cultivation of religious attitudes was implemented through spiritual habituation, teacher role modeling, ethical communication guidance, and disciplined behavior development based on the values of Manacika, Wacika, and Kayika Parisudha. Several challenges were identified, including students’ internal factors, social environmental influences, digital media exposure, and limited family involvement. The study concludes that the internalization of Hindu cultural values through Tri Kaya Parisudha serves as a strategic approach to strengthening religious character education in schools.